How Do Plants and Phytohormones Accomplish Heterophylly, Leaf Phenotypic Plasticity, in Response to Environmental Cues - Nakayama, Hokuto; Sinha, Neelima R.; Kimura, Seisuke (Frontiers in Plant Science, 2017)
Plant species are known to respond to variations in environmental conditions. Many plant species have the ability to alter their leaf morphology in response to such changes. This phenomenon is termed heterophylly and is widespread among land plants. In some cases, heterophylly is thought to be an adaptive mechanism that allows plants to optimally respond to environmental heterogeneity. Recently, many research studies have investigated the occurrence of heterophylly in a wide variety of plants. Several studies have suggested that heterophylly in plants is regulated by phytohormones. Herein, we reviewed the existing knowledge on the relationship and role of phytohormones, especially abscisic acid (ABA), ethylene, gibberellins (GAs), and auxins (IAA), in regulating heterophylly and attempted to elucidate the mechanisms that regulate heterophylly.